Biogeographic patterns of daily wildfire spread and extremes across North America - Balik, Jared A.; Coop, Jonathan D.; Krawchuk, Meg A.; Naficy, Cameron E.; Parisien, Marc-André; Parks, Sean A.; Stevens-Rumann, Camille S.; Whitman, Ellen (Frontiers in Forests and Global Change, 2024)
Climate change is predicted to increase the frequency of extreme single-day wildfire events. Spatio-temporal patterns of wildfire causes and seasonality are well documented at the resolution of final perimeters and ignition dates, but daily progression remains poorly understood across continental spatial scales, particularly for extreme single-day events (“blow ups”). Using remotely sensed daily progression of 9,636 fires ≥400 ha that occurred in the U.S. and Canada between 2002-2021, we characterized daily fire spread, extreme single-day events, duration and seasonality of fire and extreme single-day events, and ecoregional climatic niches of fire in terms of Actual Evapotranspiration (AET) and Climatic Water Deficit (CWD) annual climate normals. To explore extreme single-day events’ occurrence, extent, and impacts, we considered complementary ecoregional and continental extreme thresholds (Ecoregional or Continental Mean Daily Area Burned + 2SD). Ecoregional mean spread rates and extreme thresholds were regressed against burned areas’ AET and CWD to explore climatic influence on spread. We found three-fold differences in mean Daily Area Burned among 10 North American ecoregions, ranging from 260 ha day-1 in the Marine West Coast Forests to 751 ha day-1 in Mediterranean California. Ecoregional extreme thresholds ranged from 3829 ha day-1 to 16626 ha day-1, relative to a continental threshold of 7173 ha day-1. The 3% of events classified as extreme cumulatively account for 16-55% of total area burned among ecoregions. We observed four-fold differences in mean fire duration, ranging from 2.7 days in the Great Plains to 10.5 days in Northwestern Forested Mountains. Regions with shorter fire durations also had greater daily area burned, suggesting a paradigm of fast-growing short-duration fires in some regions and slow-growing long-duration fires elsewhere. CWD had a weak positive relationship with spread rate and extreme thresholds, and there was no pattern for AET. Although climatic conditions may set the stage for ignition, finer-scale mechanisms likely drive daily spread. Collectively, daily fire progression offers insights into the regional and seasonal distributions of extreme single-day events, as well as how they shape net fire effects.